A randomized study of twist drill versus burr hole craniostomy for treatment of chronic subdural hematomas in 100 patients - Singh, SK; Sinha, M; Singh, VK; Parihar, A; Srivastava, C; Ojha, BK; Chandra, A (Indian Journal of Neurotrauma, 2011)
Chronic subdural hematoma (CSDH) has been treated by a variety of surgical approaches like twist drill craniostomy (TDC), burr hole craniostomy (BHC), craniotomy, etc. There are large variations in cure rates and recurrence rates among the surgical options in literature and like all surgical techniques, there is a paucity of well-designed trials to sort out the issue. It is an accepted fact of surgery that the least invasive approach will often be the best approach. We set out with the hypothesis that TDC is as safe and as effective as BHC for CSDH treatment. A prospective randomized controlled trial for 100 patients was done to compare the results of TDC and BHC (both with drain) in patients of unilateral CSDH. Recurrence rate was the primary outcome variable evaluated. A strict clinic-radiological criteria was used to avoid ambiguity in the study. Forty-eight patients underwent TDC and 52 patients underwent BHC. Mortality was 2% (patients in low GCS), and 2% unexpected mortality occurred (unrelated causes). Complication rate was 14% overall and was similar in both groups. Overall outcome (primary and secondary) was comparable across both groups with no significant difference. Cost, invasiveness and duration of surgery was significantly less in the TDC group. The cure rate, recurrence rate, mortality and morbidity of TDC with drain is significantly similar to that of BHC with drain for treatment of defined patients of unilateral sub-acute and chronic subdural hematoma. The cost, duration and invasiveness of TDC surgery is significantly less than that for BHC surgery.
Keywords: burr hole; chronic subdural hematoma; twist drill